2000
DOI: 10.1080/000187300412248
|View full text |Cite
|
Sign up to set email alerts
|

Spin fluctuations and high temperature superconductivity

Abstract: Theory of spin¯uctuations for itinerant magnetism and its application to high temperature superconductivity are reviewed. After a brief introduction to the whole subject the developments of the self-consistent renormalization theory of spin¯uctuations are summarized with particular emphasis on critical properties at the quantum phase transitions. Most of the anomalous properties in the normal state of high-T c cuprates are understood as due to the critical behaviours for the two dimensional antiferromagnetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
352
2
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(378 citation statements)
references
References 85 publications
20
352
2
4
Order By: Relevance
“…The antiferromagnetic spin fluctuations described by χ s (q, iΩ n ) play a dominant role in the FLEX approximation. The characteristic results of the nearly anti-ferromagnetic Fermi liquid theory 17,53,54,55,56,59,60,72,73,75) are qualitatively reproduced within the FLEX approximation. The superconducting critical temperature T c is determined as the temperature below which the linearized Dyson-Gor'kov equation has a non-trivial solution ( Fig.…”
Section: §1 Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…The antiferromagnetic spin fluctuations described by χ s (q, iΩ n ) play a dominant role in the FLEX approximation. The characteristic results of the nearly anti-ferromagnetic Fermi liquid theory 17,53,54,55,56,59,60,72,73,75) are qualitatively reproduced within the FLEX approximation. The superconducting critical temperature T c is determined as the temperature below which the linearized Dyson-Gor'kov equation has a non-trivial solution ( Fig.…”
Section: §1 Introductionmentioning
confidence: 61%
“…57) The FLEX approximation is a conserving approximation 58) and describes the anti-ferromagnetic spin fluctuations including the mode coupling effects partly. 59,60) It has been shown that the superconducting critical temperature with a relevant order T c ∼ 100K is obtained by the FLEX approximation for High-T c cuprates. 61,62,63,64,65,66,67) The relevant results are also obtained for the organic superconductor κ-(BEDT-TTF) compounds 68,69,70) and for the ladder type compound Sr 14−x Ca x Cu 24 O 41 .…”
Section: §1 Introductionmentioning
confidence: 99%
“…It has been believed that superconductivity is mediated by antiferromagnetic (AFM) fluctuations in cuprates and heavy-fermion superconductors. [1][2][3][4] The relationship between superconductivity and AFM fluctuations in recent-discovered iron-based superconductors has also been discussed. [5][6][7][8][9][10][11][12][13][14][15][16] Up to now, it has been reported that superconductivity appears around the AFM quantum critical point in the Ba122 system, indicative of the strong relationship between superconductivity and low-energy AFM fluctuations.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] One key to making progress in this area is the identification of model material systems that are complex enough to exhibit the physics of interest but simple enough to be compared to theory. Studies of several low dimensional magnetic materials have greatly improved our understanding of QCP physics in insulating solids, [6][7][8] but our understanding of QCP phenomena in metallic systems is much less clear.…”
Section: Introductionmentioning
confidence: 99%